2019
DOI: 10.1371/journal.pone.0211580
|View full text |Cite
|
Sign up to set email alerts
|

Predicting in-hospital mortality among non-trauma patients based on vital sign changes between prehospital and in-hospital: An observational cohort study

Abstract: ObjectiveTo prevent misjudgment of the severity of patients in the emergency department who initially seem non-severe but are in a critical state, methods that differ from the conventional viewpoint are needed. We aimed to determine whether vital sign changes between prehospital and in-hospital could predict in-hospital mortality among non-trauma patients.MethodsThis observational cohort study was conducted in two tertiary care hospitals. Patients were included if they were transported by ambulance for non-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Such a decrease is associated with future clinical deterioration and the need of M/V or vasopressin with a high sensitivity [ 17 ]. One study demonstrated that prehospital hemodynamic variability was associated with clinical deterioration [ 18 ]. In another study, repeated BP measurements in the ER were related to improved outcome prediction compared to single measurements, but in the same study, repeated measurements of other vital signs failed to improve the prognostic ability [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a decrease is associated with future clinical deterioration and the need of M/V or vasopressin with a high sensitivity [ 17 ]. One study demonstrated that prehospital hemodynamic variability was associated with clinical deterioration [ 18 ]. In another study, repeated BP measurements in the ER were related to improved outcome prediction compared to single measurements, but in the same study, repeated measurements of other vital signs failed to improve the prognostic ability [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11,64,65] Several studies conclude that early changes in vital signs or scores are associated with patient outcomes like mortality or ICU admission. [11,35,[63][64][65][66] These studies show that, compared to patients with deteriorating vital signs, patients with vital sign normalization had a lower risk of mortality. Only one, however, analyzed repeated determination of vital signs in order to predict safe, early discharge.…”
Section: Scores Predicting Safe Early Discharge Are Scarcementioning
confidence: 86%
“…Multiple studies have analyzed the value of repeated vital sign measurements on patient outcome. Available studies either analyzed individual vital sign measurements [63] or combined these measurements in scores like the qSOFA or MEWS [11,35,[64][65][66]. Three studies compared single with repeated vital sign or score measurements and demonstrated that repeated measurements are superior in predicting clinical course of infectious or septic patients in the ED.…”
Section: Scores Predicting Safe Early Discharge Are Scarcementioning
confidence: 99%
“…The shock index (SI) is an indicator of the severity of hypovolemic shock and is calculated by dividing the heart rate (HR) by systolic blood pressure (SBP) [ 1 ]. It serves to predict the mortality, need for blood transfusion, or necessity of intensive care unit admission among patients with trauma [ 2 7 ], postpartum haemorrhage [ 8 , 9 ], acute myocardial infarction [ 10 , 11 ], stroke [ 12 , 13 ], sepsis [ 14 , 15 ], and other critical conditions [ 16 , 17 ]. Numerous previous studies have demonstrated that the SI demonstrates superior prediction for mortality to traditional vital signs, although it has some limitations, including its low sensitivity especially for the elderly or obstetric patients [ 2 17 ].…”
Section: Introductionmentioning
confidence: 99%